Uso potencial de microalgas para mitigar los efectos de las emisiones de dióxido de carbono (2017)
One of the alternatives to control or reduce CO2 emissions in the atmosphere is to implement microalgae culture. This paper presents a review of the results of the use of microalgae; also, describes the characteristics of the species and other factors that may influence the process. Finally, a comparison with the results obtained with larger species and with different techniques such as adsorption is made. The objective of this review is to highlight the potential use of microalgae to reduce CO2 emissions. It was found that if factors such as initial gas concentration, illumination, and temperature are appropriately controlled, the use of microalgae is highly effective in capturing and removing CO2.